Role of inflammasome activation in tumor immunity triggered by immune checkpoint blockers. (16th April 2020) - Segovia, M.; Russo, S.; Girotti, M. R.; Rabinovich, G. A.; Hill, M.
Summary: Immune checkpoint blockers improve the overall survival of a limited number of patients among different cancers. Identifying pathways that influence the immunological and clinical response to treatment is critical to improve the therapeutic efficacy and predict clinical responses. Recently, a key role has been assigned to innate immune mechanisms in checkpoint blockade‐driven anti‐tumor responses. However, inflammatory pathways can both improve and impair anti‐tumor immunity. In this review, we discuss how different inflammatory pathways, particularly inflammasome activation, can influence the clinical outcome of immune checkpoint blockers. Inflammasome activation may reinforce anti‐tumor immunity by boosting CD8 + T cell priming as well as by enhancing T helper type 17 (Th17) responses. In particular, we focus on the modulation of the cation channel transmembrane protein 176B (TMEM176B) and the ectonucleotidase CD39 as potential targets to unleash inflammasome activation leading to reinforced anti‐tumor immunity and improved efficacy of immune checkpoint blockers. Future studies should be aimed at investigating the mechanisms and cell subsets involved in inflammasome‐driven anti‐tumor responses. Abstract : Innate immunity controls anti‐tumoral responses triggered by immune checkpoint blockers (ICB). Here, we discuss recent findings suggesting a role for inflammasome activation in ICB‐based cancer immunotherapy.